Endodontic Treatment in Cases of Allergic Reaction to Rubber Dam - Debkant Jena1 , Sumit Dash1 , Lora Mishra1 , Shasrirekha G2 , Siba Prasad Jena3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The oral cavity is a complex area to handle with about thirty-two teeth, highly vascular tongue, oral mucosa,and gingival. It becomes challenging for the clinician to handle a single tooth in focus with patients movementof vascular tongue and especially in very apprehensive subjects. Hence rubber dam has proved to be a boonnot only protecting the tongue, mucosa, and gingiva but also increasing the point of focus for the clinician.Secondly, it reduces infected aerosol procedures thus protecting the clinician and the attendee. Sometimesrarely patients do have allergies to latex or rubber dam and they are not aware. Hence the clinician mustask for leading questions to rule out latex allergy. If the subject does have a latex allergy modifications arerequired before the treatment.